2006
DOI: 10.1111/j.1439-037x.2006.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum can Compensate for Chilling‐Induced Grain Loss

Abstract: Chilling during male gametophyte development in sorghum (Sorghum bicolor L. Moench) inhibits development of microspores, causing male sterility. The aim of this study was to assess the effects of night chilling on yield components in sorghum. This study identified and employed collar distance as a morphological marker of anther development following chilling. Two cultivars Buster and Bonus, were subjected to three temperature regimes (25/20°C, 25/12°C and 25/8°C) for five consecutive nights at 0 cm collar dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…2004). Furthermore, Wood et al. (2006) reported that the reduction in grain set and harvest index followed a similar trend with that of pollen viability in sorghum plants subjected to chilling treatment for 5 days at the pre‐meiotic stage of anther development.…”
Section: Discussionmentioning
confidence: 61%
“…2004). Furthermore, Wood et al. (2006) reported that the reduction in grain set and harvest index followed a similar trend with that of pollen viability in sorghum plants subjected to chilling treatment for 5 days at the pre‐meiotic stage of anther development.…”
Section: Discussionmentioning
confidence: 61%
“…These results seem to show that our A‐, B‐ and R‐lines are adapted to chilling (night temperatures from 3.5 to 8.4 °C) and the male‐fertile lines have increased the proportion of viable pollen (75 %). Wood et al. (2006) reported that temperatures between 8 °C and 12 °C during sorghum microsporogenesis caused reductions of 60–70 % in pollen viability and reductions of 40–50 % in the number of seeds per panicle.…”
Section: Resultsmentioning
confidence: 99%
“…In grain sorghum, the optimum mean temperature range for seed germination is 21-35°C, and the optimum temperature ranges are between 26-34°C and 25-28°C for vegetative growth/ development and reproductive maturity, respectively (Maiti 1996). Adverse environmental conditions, such as cold (Wood et al 2006) or high temperature stress (Prasad et al 2006a) have been shown to aVect male fertility and compromise grain yield in sorghum. The following research was undertaken in order to determine the threshold levels of chronic (season-long) and acute (short-term, coincident with microsporogenesis) high temperature stress treatments that aVect pollen fertility and seed-set in grain sorghum.…”
Section: Introductionmentioning
confidence: 99%